A note on (dis)investment options and perpetuities under CIR interest rates - Larguinho, Manuela (2013)
In this chapter, we discuss alternative ways of computing the oprions to invest in and divest from an investment project in a CIR economy (Cox et al., Ecomometrica 53(2): 385-408, 1985). Moreover, different methods of determining CIR perpetuities will also be analysed.